Sectoral effect of oil price, natural gas and LNG prices on Malaysia’s services sector - Nur Surayya bt Mohd Saudi; Ariffin bin Ismail; Saizal Pinjaman; Hasan Al-Banna bin Mohamad; Haliza bt Zahari; Aida Nasirah Abdullah (2020)
This study investigates on the impact of GDP on services sector towards oil and gas prices. This study takes account three types of energy prices, namely Brent Crude, Natural Gas and LNG, and explore the impact of these energies on the services subsectors that was ranked as the higest contibuter for Malaysia’s Gross Domestic Products (GDP). The study employed an econometrics time series analysis using ARDL estimates with time series data spanning from 1987 to 2017. The empirical findings depicted a high energy intensity services subsectors that requires high input production of oil adversely affected with oil price changes. Brent Crude price shows a negative long-run relationship with storage and communication services subsectors while no relationship detected on others services subsectors that is less energy intensity namely wholesale services and finance services with natural gas and LNG prices. The study outcomes are significant for policymakers in planning budget allocation on specific services subsectors that highly contribute to GDP. An empirical finding that absent on the highest contributor of Malaysia’s GDP namely wholesale subsectors on the fluctuating energy prices, indicates that this subsector is not depended on energy prices and potential in generating Malaysia’s GDP. However, a highly affected subsectors like storage and communication services subsectors could be assisted by providing oil subsidy and tax exemption on affected industries. This is to ensure that such external impact would not affect the production performance, as well as to ascertain betterment in aiding policymakers and safeguarding these crucial sectors.